Single Cell Isolation and Analysis - Hu, Ping; Zhang, Wenhua; Xin, Hongbo; Deng, Glenn (Frontiers in Cell and Developmental Biology, 2016)
Increasing evidence shows that the heterogeneity of individual cells within a genetically identical population can be critical to their peculiar function and fate. Conventional cell based assays mainly analysis the average responses from a population cells, while the difference within individual cells may often be masked. The cell size, RNA transcripts and protein expression level are quite different within individual cells and these variations are key point to answer the problems in cancer, neurobiology, stem cell biology, immunology and developmental biology. To better understand the cell-to-cell variations, the single cell analysis can provide much more detailed information which may be helpful for therapeutic decisions in an increasingly personalized medicine. In this review, we will focus on the recent development in single cell analysis, including methods used in single cell isolation, analysis and some application examples. The review provides the historical background to single cell analysis, discusses limitations, and current and future possibilities in this exciting field of research.